Marine submicron aerosol gradients, sources and sinks - Ceburnis, Darius; Rinaldi, Matteo; Ovadnevaite, Jurgita; Martucci, Giovanni; Giulianelli, Lara; O'Dowd, Colin D. (Copernicus GmbH, 2016)
Aerosol principal sources and sinks over eastern North Atlantic waters were studied through the deployment of an aerosol chemistry gradient sampling system. The chemical gradients of primary and secondary aerosol components - specifically, sea salt (SS), water-insoluble organic matter (WIOM), water-soluble organic matter (WSOM), nitrate, ammonium, oxalate, amines, methanesulfonic acid (MSA) and water-soluble organic nitrogen (WSON) - were examined in great detail. Sea salt fluxes were estimated by the boundary layer box model and ranged from 0.3 to 3.5 ng m(-2) s(-1) over the wind speed range of 5-12 m s(-1) and compared well with the derived fluxes from existing sea salt source parameterisations. The observed seasonal pattern of sea salt gradients was mainly driven by wind stress in addition to the yet unquantified effect of marine OM modifying fractional contributions of SS and OM in sea spray. WIOM gradients were a complex combination of rising and waning biological activity, especially in the flux footprint area, and wind-driven primary sea spray production supporting the coupling of recently developed sea spray and marine OM parameterisations.